PERAN PEMERINTAH DAERAH DALAM DALAM KONTEKS EKSPRESI BUDAYA TRADISIONAL DALAM PERLINDUNGAN HAK CIPTA (Studi terhadap Peraturan Daerah Provinsi Jawa Barat Nomor 10 Tahun 2018) - Takarada, Yudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Whereas the regulation on Intellectual Property Rights law has been universally applied and accepted by the members of the World Trade Organization (WTO) by making separate rules into the positive law of each WTO member country. The existence of West Java Provincial Regulation Number 10 of 2018 concerning Intellectual Property Management including Traditional Cultural Expressions in it, can mean that the said Regulation acts as a